MANAJEMEN KOMITE OLAHRAGA NASIONAL INDONESIA DALAM PENINGKATKAN PRESTASI OLAHRAGA - Jon Herman S (Manajer Pendididikan, 2015)
The purpose of this research is to describe the Indonesian National Sport Committee Management in Lubuklinggau City. This research used qualitative descriptive methode. Thesubjek of the study were “KONI” excecutive, coches, athlets, and head of Sport and youth City Office of the research. The results of this research show that Indonesian National Sport Committee Management has been planned well, sistimatic and organized and supported by appropriate organizing. So, in applying the program the management always monitored and evaluated with reguler schedule, although there are some trials wich they had to face thus there are some supporting, factors in Indonesian National Sport Committe Management Organization as well.Keyword: management, indonesian national sport committe